Analysis of Power Transformer Insulation Resistance Using the Applied Voltage test Method - Feri, Mohammad; Jamaaluddin, Jamaaluddin; Ayuni, Shazana Dhiya (Faculty of Engineering, Universitas Tanjungpura, 2025)
This study investigates insulation resistance failures in newly manufactured power transformers at PT XYZ, focusing on the application of Applied Voltage Test as the main method to detect potential insulation failures. Different from previous studies that focus more on transformers that have been in operation for a long time, this study identifies that insulation failure in new transformers can be caused by production factors, such as insulation paper degradation due to exposure to temperature and humidity during the manufacturing process. The research was conducted through direct observation, structured interviews with testing technicians, and comparative analysis of two transformer units. The test results showed significant differences between the two units, where Transformer Unit 2 failed the test due to insulation paper degradation, which was confirmed through physical inspection. This study emphasizes the importance of Applied Voltage Test in identifying insulation defects at an early stage and shows that the quality of materials and production processes greatly affect the reliability of transformers. The findings make new contributions to understanding the causes of insulation failures in new transformers, as well as provide practical recommendations for optimization of test methods and improvement of production quality, thereby minimizing the risk of insulation failures in new transformers. Furthermore, this research highlights the significance of early detection through Polarization Index testing, which can serve as an indicator of insulation degradation. These insights are crucial for improving quality control in transformer manufacturing and ensuring the reliability of power distribution systems.